Risk Management of Schools Under the Secondary Educational Service Area Office Kanchanaburi - Auemsaart ์Namfon; Pumklom, Mitparnee (Journal of Graduate MCU KhonKaen Campus, 2023)
The purposes of this research were 1) to risk management in schools under The Secondary Educational Service Area Office Kanchanaburi. and 2) to compare risk management in schools under The Secondary Educational Service Area Office Kanchanaburi by divided to the school sizes. The sample consisted of 308 teachers in schools under the Secondary Educational Service Area Office Kanchanaburi, obtained by stratified random sampling according to school size. The research instrument was a five-level rating scale questionnaire with content validity between 0.67-1.00 and a reliability of 0.99. The statistics under in the data analysis were percentage, mean, standard deviation. The data were treated with one-way analysis of variance and found the difference of the means, and paired tests were carried out according to Scheffe’s method. The statistical significance level was set at 0.05. The findings were as follows: 1. Risk management of schools under the Secondary Educational Service Area Office Kanchanaburi, overall and in each individual aspect were at a high level, ranking in mean from high to low as performance, strategy, budget and rule and regulation management aspect. 2. The comparison risk management of schools under the Secondary Educational Service Area Office Kanchanaburi classified by school size, overall risk management of schools there was no statistically significant difference.